Socioeconomic impact on Kampung Baru: revisiting the policy for the new Malaysia - Syahmi @ Muhammad Syahmi Jaafar,; Adam Abu Hanipah,; Chong, Ka Foo (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Kampung Baru represent a type of settlement that is unique to Peninsular Malaysia.This terms refer to villages built during the emergency as a military strategy under the Emergency Ordinance and also known as the Briggs Plan (1948-1960).The main aim of this article is to investigate the effects of development projects implementation on New Village at Peninsular Malaysia in Year 2017. In 2002, the Kajian Pelan Induk Kampung Baru (PIKB) was implemented under the designation of the Economic Planning Unit (EPU). PIKB's main objective is to integrate the new village in terms of physical, social, economic and political in the flow of state development. At the same time, taking into account the traditions, culture and historical value of Kampung Baru, strategies to perpetuate the features of Kampung Baru that have the potential to be developed as a tourist attraction are also taken. The objectives of this article are; to investigate the impact and effectiveness of construction of infrastructure, socioeconomics and landscaping facilities in Kampung Baru; to assess the level of satisfaction of the Kampung Baru residents towards the Kampung Baru development program which has been implemented; and to examine the problem of infrastructure, socioeconomics and landscaping facilities faced by the residents of Kampung Baru. After 9th May 2018 seems the new dawn of Malaysia, the new Government may have a new policy in alleviating Kampung Baru to a new dimension. It is a hope that this article can give clear perspective and way forward on the socioeconomic impact of Kampung Baru with the new government policy.